2020
DOI: 10.1016/j.ajhg.2020.10.004
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of Parental Perceptions of Rapid Whole-Genome and -Exome Sequencing among Seriously Ill Infants

Abstract: Rapid diagnostic genomic sequencing recently became feasible for infants in intensive care units (ICUs). However, research regarding parents' perceived utility, adequacy of consent, and potential harms and benefits is lacking. Herein we report results of parental surveys of these domains from the second Newborn Sequencing in Genomic Medicine and Public Health (NSIGHT2) study, a randomized, controlled trial of rapid diagnostic genomic sequencing of infants in regional ICUs. More than 90% of parents reported fee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
75
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(75 citation statements)
references
References 32 publications
0
75
0
Order By: Relevance
“…38 As previously noted, to achieve optimal reductions in morbidity and mortality, rapid genomic sequencing must be implemented within a comprehensive precision medicine delivery system. 38 Finally, NSIGHT2 examined clinician perceptions of some potential harms of rapid genomic sequencing 35 (parental perceptions of the benefits and harms of rapid genomic sequencing in the NSIGHT2 study are reported in the accompanying paper 36 ). When surveyed regarding their perceptions of increased stress or confusion among families or clinical staff as a result of genomic sequencing, clinicians reported this in only 3% of cases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…38 As previously noted, to achieve optimal reductions in morbidity and mortality, rapid genomic sequencing must be implemented within a comprehensive precision medicine delivery system. 38 Finally, NSIGHT2 examined clinician perceptions of some potential harms of rapid genomic sequencing 35 (parental perceptions of the benefits and harms of rapid genomic sequencing in the NSIGHT2 study are reported in the accompanying paper 36 ). When surveyed regarding their perceptions of increased stress or confusion among families or clinical staff as a result of genomic sequencing, clinicians reported this in only 3% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…35 Parental perceptions of benefits and harms in the NSIGHT2 study are reported in the accompanying article. 36 Here we report clinician perceptions of benefits and harms of genomic sequencing in infants. Of 207 clinician responses, 84 (41%) disclosed that diagnostic genomic sequencing improved communication with families regarding infant outcomes, expectations, and prognosis.…”
Section: Changes In Communication and Confirmatory Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, parents placed strong value on negative test results, emphasizing that diagnostic yield is not a good proxy for parental perceived utility. 76 Nondiagnostic results can still be useful to help exclude (or make less likely) genetic conditions that may have prognostic implications (e.g., increased risk of seizures, cancer, or vision loss as examples) or other clinical management (e.g., contraindication to anesthesia/surgery).…”
Section: Diagnostic Yieldmentioning
confidence: 99%
“…Of these, 105 were excluded based on lack of empirical results, or study designs that focused on hypothetical response to genetic testing, pre-test perceptions of genetic testing, and/or non-parent/caregiver reported outcomes. Thirty-three [ 15 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ] met all inclusion criteria Figure 1 . All full texts were reviewed for inclusion by two independent reviewers, with an inter-rater agreement of 83.4%.…”
Section: Resultsmentioning
confidence: 99%